GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI PONPES BAITURRAHMAN, DESA TEJA TIMUR, KECAMATAN PAMEKASAN, KABUPATEN PAMEKASAN TAHUN 2025 - Yunita Kholilaili Saras Wati; Nurvy Alief Aidillah; Lianita Primi Octaviana (Rena Cipta Mandiri, 2025)
Adolescence is a transition phase from childhood to adulthood. In this phase, adolescents experience puberty, which is marked by hormonal changes and physical transformation. One of the organs that develops in adolescent girls is the breast. Breast cancer is the fifth leading cause of cancer death worldwide. Early detection can be done with BSE (breast self-examination). In today's society, many women, especially adolescent girls, have not performed breast self-examination (BSE) due to lack of knowledge. In this study, the type of research conducted was descriptive with a survey method. The instrument was a questionnaire consisting of systematically designed questionnaires. The sample was 29 people and the results showed that 82.76% had less knowledge of BSE examinations. Lack of knowledge among adolescents requires health workers to provide education to the community about early detection or screening of breast cancer cases through SADARI, with the aim of changing behavior and increasing public awareness about the importance of early detection of breast cancer.